Retinopathy of Prematurity - Neonatologists’ Experience - Akter, S; Hossain, MM; Shirin, M; Anwar, KS (Journal of Bangladesh College of Physicians and Surgeons, 2014)
In Bangladesh advancement of neonatal care has increased the survival of preterm very low birth weight (VLBW) neonates and the incidence of Retinopathy of prematurity (ROP) is also increasing. The objective of this study was to identify the cases of ROP and their risk factors recorded during hospital stay. This was a prospective observational study at special care baby unit (SCABU) and Intensive care unit of Dhaka Shishu Hospital from July, 2006 to March, 2008 among premature (<34 weeks) and/or VLBW (<1500 gm) neonates. Neonates who fulfilled the inclusion criteria were followed up daily to record certain clinical factors, investigation findings and medications. Discharged neonates had repeated ophthalmological examinations as advised by the ophthalmologist. Main outcome measure was abnormal findings on ophthalmoscopic examinations. Infants were divided into Normal group that included newborns without ROP, and Abnormal group that included newborns with ROP. Comparative analysis of recorded clinical factors was done between the two groups. Initial enrollment comprised of 129 neonates but the study was completed by 58 due to death and drop out. Normal group had 35(60%) and Abnormal group had 23(40%) neonates. VLBW, oxygen in high flow rate, mean total hours of oxygen inhalation, mean percentage of inhaled oxygen (FiO2), mean percent saturation of hemoglobin with oxygen (SpO2), frequency of apnoeic attacks managed with of bag and mask ventilation , mechanical ventilation, culture proven septicaemia, cumulative volume of blood transfusion, and intra ventricular hemorrhage (IVH) > grade II were significantly related with ROP. Stepwise logistic regression analysis revealed VLBW [p=.004, Odds Ratio (OR), .33; Confidence Interval (CI), 0.14 to.436], apnoeic attacks managed with bag and mask ventilation (p=.023; OR,14.2; CI, 12.71 to 26.54), cumulative volume of blood transfusion (p=.013; OR,.43; CI, .028 to .653), and culture proven septicaemia (p=.005; OR,4.0 CI, 2.50 to 9.99) to be most significant factors. Awareness should be increased among neonatologists and ophthalmologists regarding screening and treatment of ROP. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21001 J Banagladesh Coll Phys Surg 2013; 31: 181-188